2017
DOI: 10.3390/f9010016
|View full text |Cite
|
Sign up to set email alerts
|

Forest Floor and Mineral Soil Respiration Rates in a Northern Minnesota Red Pine Chronosequence

Abstract: Abstract:We measured total soil CO 2 efflux (R S ) and efflux from the forest floor layers (R FF ) in red pine (Pinus resinosa Ait.) stands of different ages to examine relationships between stand age and belowground C cycling. Soil temperature and R S were often lower in a 31-year-old stand (Y31) than in 9-year-old (Y9), 61-year-old (Y61), or 123-year-old (Y123) stands. This pattern was most apparent during warm summer months, but there were no consistent differences in R FF among different-aged stands. R FF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Since tree height can be used as a proxy of GPP, the high SR rate in this site could be attributed to high GPP [ 11 , 31 , 71 , 84 86 ], which can provide substrates for root and microbial respiration through photosynthesis [ 71 , 87 ], supported by a significant positive relation between SR ref and dominant tree height ( Fig 5 and Table 5 ). Above- and below-ground tree size increases with age and, therefore, the growth of root biomass leads to higher SR as forest stands develop [ 39 , 88 90 ]. In this context, our findings suggest that after removing the effect of temperature, productivity and tree size are principal factors affecting SR.…”
Section: Discussionmentioning
confidence: 99%
“…Since tree height can be used as a proxy of GPP, the high SR rate in this site could be attributed to high GPP [ 11 , 31 , 71 , 84 86 ], which can provide substrates for root and microbial respiration through photosynthesis [ 71 , 87 ], supported by a significant positive relation between SR ref and dominant tree height ( Fig 5 and Table 5 ). Above- and below-ground tree size increases with age and, therefore, the growth of root biomass leads to higher SR as forest stands develop [ 39 , 88 90 ]. In this context, our findings suggest that after removing the effect of temperature, productivity and tree size are principal factors affecting SR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also described effects of tree size on F CO2 in forest ecosystems, generally finding higher F CO2 in the immediate neighborhood of larger trees [25][26][27][28][29][30]. However, counterexamples exist [10,31], and several chrono sequence studies have found reduced F CO2 with stand age in even-aged plantations [32,33], or no consistent relationship [34]. Rodríguez-Calcerrada et al, [35] tested for associations between visible crown health indicators and F CO2 in an open woodland in Spain but found that increased plant recruitment near declining trees offset potential reductions in F CO2 related to tree decline.…”
Section: Introductionmentioning
confidence: 99%
“…However, counterexamples exist [e.g., 10,31], and several chronosequence studies have found reduced FCO2 with stand age in even-aged plantations [e.g., 32,33], or no consistent relationship [e.g., 34]. Rodríguez-Calcerrada et al, [35] [36], and there is evidence for declines in whole-tree leaf area through ontogeny [37].…”
Section: Introductionmentioning
confidence: 99%